NiOx nanoparticles supported on polyethylenimine functionalized CNTs as efficient electrocatalysts for supercapacitor and oxygen evolution reaction - Cheng, Yi; Shen, P.; Jiang, San Ping (Elsevier Ltd, 2014)
Ni oxide based nanoparticles (NPs) have been widely used as electrocatalysts in the electrochemical energy storage and conversion applications. In this paper, NiOx NPs are successfully synthesized by the self-assembly of Ni precursor onto polyethylenimine functionalized carbon nanotubes (PEI-CNTs) assisted with microwave radiation. NiOx NPs with size around 2–3 nm are homogenously dispersed on the PEI-CNTs supports with no aggregation. The electrochemical activity of NiOx NPs on PEI-CNTs, NiOx/PEI-CNTs, as effective electrocatalysts is studied for supercapacitor and oxygen evolution reaction in alkaline solutions. NiOx/PEI-CNTs show a capacitance of 1728 and 1576 F g−1 based on active material, and 221 and 394 F g−1 based on total catalyst loading on 12.5% and 25% NiOx/PEI-CNTs, respectively, which is substantially higher than 152 F g−1 of unsupported NiO. The NiOx/PEI-CNTs electrodes exhibit reversible and stale capacitance of ~1200 F g−1 based on active materials after 2000 cycles at a high current density of 10 A g−1. NiOx/PEI-CNTs also exhibit significantly higher activities for oxygen evolution reaction (OER) of water electrolysis, achieving a current density of 100 A g−1 at an overpotential of 0.35 V for 25% NiOx/PEI-CNTs. It is believed that the uniformly dispersed nano-sized NiOx NPs and synergistic effect between the NiOx NPs and PEI-CNTs is attributed to the high electrocatalytic performance of NiOx/PEI-CNTs electrocatalysts. The results demonstrate that NiOx NPs supported on PEI-CNTs are highly effective electrocatalysts for electrochemical energy storage and conversion applications.